Spontaneous innominate artery rupture in a patient with systemic sclerosis. Issue 8 (18th August 2022) - Ali, Sabreen; DeVile, Michael; Hughes, Rodney
ABSTRACT: We present the case of a 57-year-old female with systemic sclerosis who presented in extremis to our hospital with an acute onset of right upper chest and neck pain with swelling. She deteriorated rapidly due to haemodynamic compromise from suspected bleeding and suffered a cardiac arrest with prolonged resuscitation. Emergency thoracotomy demonstrated an acute longitudinal tear of the innominate artery/brachiocephalic trunk at the junction of the subclavian and common carotid arteries. This is the first reported case of spontaneous arterial rupture in a patient with systemic sclerosis, and while direct causation is difficult to prove, her history of previous vascular complications with potential ongoing microvascular damage makes a contributory role likely.